(untitled) (Fiep Bulletin - online, 2015)
The practice of physical activity for people with disabilities’ conditions can provide several benefits, in special, emotional and social. The objective was to evaluate the social and emotional competencies of people with physical disability’s conditions who participate of a wheelchair basketball group. This research was characterized as descriptive-exploratory. The participants of the research had been composed for 10 people with physical disability’s conditions, integrant of an AFLODEF wheelchair basketball group. They had been selected in an intentional way, according to inclusion’s criteria: to belong to the age between the 25 and 55 years old and to integrate the group that practices wheelchair basketball at least 6 months. As measure’s instrument was used the questionnaire How Mapping Your Emotional Intelligence (COOPER; SAWAF, 1997) and it was elaborated a Psychometric Questionnaire about the social-affective acceptance in the sports scope (MORENO, 1972; BELTRAME, 2000). It was used the Descriptive Statistics, through simple and relative frequency, and mean. In this regard the social competence, the group did not present leaders, but there is one sub leader. No athlete was considered isolated and 8 were considered rejected for the group. There is a reciprocal choice, between two more voted athletes. And concerning to the emotional competence, the athletes presented powerful competencies in the Intentionality, Creativity, Interpersonal Connections and Discontent Constructive, in the most of the situations and even under pressure. Nevertheless, they presented difficulties in the Resilience aspect. It was perceived still that the difference between the interpersonal connections and the relations between the group’s integrant derives from disillusions and conflicts, as well as of the preference and probable migration of some integrants for others modalities. In this way, it believes that the good affinity between the group’s members like an essential factor for the persistence in a physical activity, what allows us to affirm that occur an improvement in the quality of life of these people. Furthermore that it can infer that the participants of this research had interpersonal relationships of good quality in childhood, and the practice of the physical activity had proportionate chances for the personal and social development of these.